ROMAN 2005. IEEE International Workshop on Robot and Human Interactive Communication, 2005.
DOI: 10.1109/roman.2005.1513798
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy emotion recognition in natural speech dialogue

Abstract: Abstract-This paper describes the realization of a natural speech dialogue for the robot head MEXI with focus on its emotion recognition. Specific for MEXI is that it can recognize emotions from natural speech and also produce natural speech output with emotional prosody. For recognizing emotions from the prosody of natural speech we use a fuzzy rule based approach. Since MEXI often communicates with well known persons but also with unknown humans, for instance at exhibitions, we realized a speaker-dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 8 publications
1
6
0
2
Order By: Relevance
“…The cross-corpora evaluation in Shami and Verhels [15] demonstrated the drop in classification performance observed when training on one emotional corpus and testing on another. Other studies have shown similar results [5], [16]- [18]. Several approaches have been proposed to solve this problem.…”
Section: Related Worksupporting
confidence: 56%
“…The cross-corpora evaluation in Shami and Verhels [15] demonstrated the drop in classification performance observed when training on one emotional corpus and testing on another. Other studies have shown similar results [5], [16]- [18]. Several approaches have been proposed to solve this problem.…”
Section: Related Worksupporting
confidence: 56%
“…For example, Razak [11] used 22 emotion features to recognize emotions, and the average recognition rate was 68.59%. Austermann [13] has done research on robot emotion recognition in the natural speech dialogue, membership functions were used to select the most significant features from a set of twenty analyzed features. Austermann [13] has done research on robot emotion recognition in the natural speech dialogue, membership functions were used to select the most significant features from a set of twenty analyzed features.…”
Section: Related Work Comparisonmentioning
confidence: 99%
“…Austermann [13] has done research on robot emotion recognition in the natural speech dialogue, membership functions were used to select the most significant features from a set of twenty analyzed features. Moreover, in speaker-independent system, the average recognition rate for six emotion states we got is higher than that for four emotion states in paper [13]. In this paper, with the method we proposed, we get a high average recognition rate of 78.6% for six emotion states in speaker-independent system.…”
Section: Related Work Comparisonmentioning
confidence: 99%
“…Otros propósitos del uso de señales de voz es la formulación e implementación de sistemas para la distinción del habla [7]- [9], reconocimiento del habla [10], reconocimiento de lenguaje [11], reconocimiento de emociones basados en habla y en género [12], [13], diagnóstico de enfermedades patológicas como la disfonía y la laringitis [14], diagnóstico de nódulos, edemas y parálisis unilateral de las cuerdas vocales [15], reconocimiento de disartria en sistemas de reconocimiento automático de habla [16] y la detección temprana de Parkinson mediante voz [17].…”
Section: Introductionunclassified